Tathwîr Washîlah Aflâm Qashîrah Fî Ta’lîm Al-Mufradât - Ita Khoerunnisa; Zaki Ghufron (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
The purpose of this study was to develop audiovisual-based learning media, namely short films for vocabulary learning in the profession chapter for the eighth grade and to determine the effectiveness of the product. This research was conducted at MTs Al-Wathoniyah 20 Bekasi. The method used in this research is research and development using the Borg and Gall development procedure which is summarized into four steps, namely 1) information gathering stage, 2) planning stage, 3) product development stage, 4) validation and trial stage. Data collection techniques using questionnaires, tests, and interviews. The test of short film audiovisual media in vocabulary learning uses a test as an instrument. The average result of the students' pre-test scores was 44.41, and the average results of the students' post-test scores was 57.65. Judging from the post-test results of students who experienced an increase, audiovisual media in the form of short films was effective to be used in the Arabic language learning process in class VIII MTs Al-Wathoniyah 20 Bekasi.